Model Pembelajaran Hadis Di Pondok Pesantren (Studi Perbandingan Pondok Pesantren Annajiyah Dan Ulul Albab Lubuklinggau) - Karomi, Arita Alfa; Hasanah, Uswatun; adriasyah, Adriansyah (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2023)
The Hadith Learning Model at Islamic Boarding Schools (Comparative Study of Ulul Albab Lubuklinggau Islamic Boarding School) is the title of this thesis. The lack of research on the Hadith Learning Model in Islamic Boarding Schools inspired this research. Considering that Islamic boarding schools are the birthplaces of religious experts, scholars and hadiths, it is important to evaluate hadith studies there. Ulul Albab and Annajiyah Islamic Boarding Schools play an important role in the teaching of hadith. This can be seen from the fact that the Annajiyah Islamic boarding school follows the Gontor Islamic boarding school curriculum. Because the founder of the Annajiyah Islamic Boarding School is a Gontor graduate, this pesantren is different from the Ulul Albab Islamic Boarding School which follows the Ministry of Religion's K13 curriculum for learning hadith. citing studies on hadith learning strategies, hadith learning themes, and books. Field research was conducted at Ulul Albab Lubuklinggau and Annajiyah Islamic Boarding School. The results of the study found that the Annajiyah Islamic boarding school used two hadith reference books, one for grades 9-12 Bulugul Maram and another for grades 7-8 KMI Gontor. Grade 7 hadith themes, 32 hadiths, and 4 hadiths for education. Engagement and memorization methods for grades 7 to 8. The deliberation method for grades 9 Classes 10-12 uses the question and answer method. Grades 7-8 at the Ulul Albab Islamic Boarding School, grades 9 at Arbain Nawawi, and grades 10-12 at Bulugul Maram teach noble character. Aqidah hadith contains 14 hadiths for grade 7, fiqh hadith contains 14 hadiths for grade 8, and mu'amalah hadith contains 4 hadiths and tazkiyatun nafs contains 8 hadiths for grade 9. Class 10 Kitabu at-Thaharah contains nine subchapters about 52 fiqh hadiths. 57 hadiths are discussed in Kitabu as-Shalah Class 11 subchapter 9. 28 hadiths are discussed in Kitabu az-zakah Class 12 with the topic of fiqh. Singing/singing method for grades 7-9, lecture and question and answer method for grades 10-12.